Association between smoking and in-hospital mortality in patients with acute myocardial infarction: results from a prospective, multicentre, observational study in China - Hao Wang; Chenxi Song; Rui Fu; Kefei Dou; Jingang Yang; Haiyan Xu; Xiaojin Gao; Shuai Liu; Xiaoxue Fan; Yuejin Yang (BMJ Open)
Introduction Smoking is a well-established risk factor for cardiovascular disease. However, the effect of smoking on in-hospital mortality in patients with acute myocardial infarction (AMI) who are managed by contemporary treatment is still unclear.Methods A cohort study was conducted using data from the China AMI registry between 2013 and 2016. Eligible patients were diagnosed with AMI in accordance with the third universal definition of MI. Propensity score (PS) matching and multivariable logistic regression were used to control for confounders. Subgroup analysis was performed to examine whether the association between smoking and in-hospital mortality varies according to baseline characteristics.Results A total of 37 614 patients were included. Smokers were younger and more frequently men with fewer comorbidities than non-smokers. After PS matching and multivariable log regression analysis were performed, the difference in in-hospital mortality between current smokers versus non-smokers was reduced, but it was still significant (5.1% vs 6.1%, p=0.0045; adjusted OR 0.78, 95% CI 0.69 to 0.88, p<0.001). Among all subgroups, there was a trend towards lower in-hospital mortality in current or ex-smokers compared with non-smokers.Conclusions Smoking is associated with lower in-hospital mortality in patients with AMI, even after multiple analyses to control for potential confounders. This ‘smoker’s paradox’ cannot be fully explained by confounding alone.Trial registration number NCT01874691.